2020
DOI: 10.1155/2020/2697230
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Eight Respiratory Bacterial Pathogens Based on Multiplex Real-Time PCR with Fluorescence Melting Curve Analysis

Abstract: Background and Objective. Acinetobacter baumannii, Escherichia coli, Klebsiella pneumoniae, Streptococcus pneumoniae, Haemophilus influenzae, Staphylococcus aureus, Pseudomonas aeruginosa, and Mycobacterium tuberculosis are primary respiratory bacterial pathogens contributing to morbidity and mortality in developing countries. This study evaluated the diagnostic performance of multiplex real-time PCR with fluorescence melting curve analysis (MCA) assay, which was used to detect eight respiratory bacterial path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
0
11
0
1
Order By: Relevance
“…pneumoniae, H. influenzae, E. coli, Staph. aureus and Pseudomonas aeruginosa are the main bacterial species that have been frequently reported to cause respiratory infections associated with morbidity and mortality in developing countries (12).…”
Section: Introductionmentioning
confidence: 99%
“…pneumoniae, H. influenzae, E. coli, Staph. aureus and Pseudomonas aeruginosa are the main bacterial species that have been frequently reported to cause respiratory infections associated with morbidity and mortality in developing countries (12).…”
Section: Introductionmentioning
confidence: 99%
“…This allows us to overcome the use of high doses of nanomaterials, otherwise low safe doses in conjugation with natural benefit materials as the combination of ZnONPs with Curcumin and enable to inhibit the viability of virulent genes expression as detected here by PCR. Similarly, the PCR enables the rapid detection of pathogens' genes as recommended by Hu et al (2020), Hassan et al (2021Hassan et al ( , 2022 who found that the use of nanocomposites with natural plant materials caused significant changes in aflatoxin regulatory genes. Other studies illustrated that the traditional antifungals and herbs against C. albicans increased the activity of secreted proteinase (Sap) and SAP genes, which can be observed by PCR (Copping et al 2005;Saleh 2011).…”
Section: Resultsmentioning
confidence: 99%
“…We have also demonstrated that the sensitivity of this assay is considerably higher than that of standard qPCR (LoD of approximately 64 CFU/mL). (11,12) It is a limitation of this study that the Droplet Reader only has two channels, which makes it di cult to do a probe-based multiplexing with more than two targets. However, a recent study by Nyaruaba et al 2021 has demonstrated that an amplitude multiplexing is possible for different SARS-CoV-2 applications by varying the primer-probe concentrations for each target.…”
Section: Discussionmentioning
confidence: 99%